(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2022)
The genesis, legislative enshrining in the norms of international legislation and the Constitution of Ukraine of the national process regarding the provision and implementation of the right to professional legal assistance in the criminal proceedings of Ukraine, as well as the state of the procedural mechanism for collecting evidence by the defense party, have been studied. The method of comparison has been applied with respect to the previous criminal procedural legislation of 1960 and the current Criminal Procedure Code of Ukraine of 2012 on the issues raised. At the retrospective level, existing problematic issues of the procedural mechanism for collecting and obtaining evidence by the defense at the stage of pre-trial investigation have been investigated. For this purpose, it has been clarified the powers of the defense party, including defense counsel, suspect, accused, convicted, acquitted person, person in respect of whom the use of compulsory medical or educational measures are envisaged or the issue of their use has been decided, as well as person in respect of whom the issue of extradition to a foreign state is to be considered, to collect evidence. At the same time, the scientific positions of scientists and representatives of scientific schools, the results of the existing discussion on the raised problematic and promising issues have been investigated. Based on the results of the research, a number of proposals and recommendations for improving theoretical and applied issues in the researched direction have been developed and proposed. Attention has been drawn to the fact that the Criminal Procedure Code of Ukraine enshrines provisions according to which the defense is granted the right to collect factual data significant for criminal proceedings, but at the same time, the procedural form of implementing this right is not fully provided for, which is the subject to legislative clarification. In the course of discussion, the suggestions of the scientists regarding the elimination of the inconsistency between the use and application of the phrase “the right to professional legal assistance”, which is enshrined in the Basic Law of Ukraine, but not implemented and used in the current Criminal Procedure Code of Ukraine and other legislative acts, have been supported. It has been proposed to eliminate the indicated inconsistencies in a legislative manner.